1984
DOI: 10.1172/jci111444
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in very low, low and high density lipoproteins in hypertriglyceridemia. Reversal toward normal with bezafibrate treatment.

Abstract: A s bstract. The effects of triglyceridemia on plasma lipoproteins were investigated in 16 hypertriglyceridemic (HTG) subjects (222-2,500 mg/dl) before and after the initiation ofbezafibrate therapy. Bezafibrate caused a mean reduction of 56% in plasma triglyceride and increased the levels of lipoprotein and hepatic triglyceride lipases by 260 and 213%, respectively. The natures of very low density lipoprotein (VLDL), isolated at plasma density and of low and high density lipoprotein (LDL and HDL), separated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
96
0
4

Year Published

1985
1985
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(111 citation statements)
references
References 54 publications
11
96
0
4
Order By: Relevance
“…Numerous studies have demonstrated their association with extensive, pro-atherogenic changes of LDL and HDL. 13,35,36 In addition there is evidence that large VLDL can themselves promote cholesterol accumulation by cells. 37 Modulation of the LDL pro®le, notably the presence of small, dense LDL particles, has attracted widespread attention because of the links with coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated their association with extensive, pro-atherogenic changes of LDL and HDL. 13,35,36 In addition there is evidence that large VLDL can themselves promote cholesterol accumulation by cells. 37 Modulation of the LDL pro®le, notably the presence of small, dense LDL particles, has attracted widespread attention because of the links with coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in LDL particle size and density have been characterized using a variety of techniques 97 -99 and have been associated with differences in plasma triglyceride levels. 100 - 101 Distinct subclasses of LDL particles have been identified by density gradient ultracentrifugation 97 and by gradient gel electrophoresis; the latter technique separates LDL particles by size and charge, 102 and has allowed the identification of two LDL subclass patterns, denoted patterns A and B. 103 Pattern A is characterized by a predominance of relatively large, buoyant, LDL subclasses in individual subjects, while pattern B is characterized by a predominance of small, dense, LDL particles.…”
Section: Low Density Lipoprotein Subclass Patternsmentioning
confidence: 99%
“…Furthermore, it has been shown that a less dense HDL2 subfraction (relative high lipid/apolipoprotein ratio) is epidemiologically associated with reduced coronary heart disease, while a more dense HDL 3 subfraction (relatively low lipid/ apolipoprotein ratio) is thought to be unrelated to such disease (22,23). Nevertheless, recent studies have shown that HDL in individuals with hypertriacylglycerolaemia mainly consist of HDL 3 , which are enriched with apolipoproteins and triglycerides and which are depleted of cholesterol (24). Furthermore, it has been reported that alcohol consumption, which is known to be associated with high HDL cholesterol (25 -27) and frequently with hypertriacylglycerolaemia (28, 29), mainly resulted in an enhanced level of HDL 3 mass without affecting HDL 2 mass (30).…”
Section: Discussionmentioning
confidence: 99%